(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The article undertakes a comprehensive analysis of the regulatory framework governing the nutrition system for children in school settings in Ukraine. This analysis is primarily based on Resolution No. 305, "On the Approval of Norms and the Procedure for Organizing Nutrition in Educational Institutions and Children’s Health and Recreation Institutions," dated March 24, 2021, and Order No. 2205, "On the Approval of the Sanitary Regulations for General Secondary Education Institutions," dated September 25, 2020. The study addresses the practical implementation of these regulations, proposing necessary amendments and additions to eliminate ambiguities and regulate certain aspects of food production and consumption. This study employs a comprehensive analytical approach to examine the provisions of the aforementioned regulatory documents. The analysis reveals inconsistencies in the current regulatory framework, which hinder the effective implementation of the school nutrition reform. Notably, the study highlights the lack of clear guidelines on the use of certain food products as raw materials for children’s meals. It emphasizes the need for a detailed list of permitted spices and seasonings to improve the palatability of dishes that are low in salt and sugar. Additionally, the research underscores the necessity for precise regulations regarding the type of chocolate allowed for school-aged children and the conditions under which it can be consumed. The study’s findings underscore the importance of harmonizing the regulatory norms to ensure coherent and practical guidelines for school nutrition. This research contributes to the ongoing reform of the school nutrition system in Ukraine by providing a critical assessment of the current regulatory norms and proposing practical amendments to enhance their effectiveness. The study’s originality lies in its detailed examination of the practical implementation challenges and its focus on harmonizing regulatory documents to improve the quality of nutrition provided in educational institutions. By addressing these issues, the study aims to support the development of a healthier future generation and foster a more effective school nutrition system.The article concludes that while significant strides have been made in reforming the school nutrition system, further refinement of the regulatory framework is essential. Recommendations include creating exhaustive lists of permissible ingredients, clear guidelines for menu planning, and addressing ambiguities in current regulations to improve the quality of school nutrition.